Model Uncertainty. Learning, and the Gains from Coordination. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
The paper considers gains from international economic policy coordination when there is uncertainty concerning the functioning of the world economy, but also learning about the 'true' model on the part of policymakers. The paper reports estimates of plausible alternative versions of a standard, two-country model. Activist policy (either coordinated or uncoordinated) may produce large welfare losses in the absence of learning, if policymakers believe in the wrong model; hence exogenous money targets and freely flexible exchange rates may be best. However, model learning (from observations on macroeconomic variables) causes coordinated policies to dominate activist uncoordinated policies or exogenous money targets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet